THE EFFECT OF COMPENSATION AND JOB SATISFACTION ON EMPLOYEE LOYALTY IN THE CITY OF SURABAYA - Agung Firmansyah; Ana Lailatul Fitriya; Aisyah Nuururrohmah Ulluwiyah; Aryinda Rif'ani; Riyan Sisiawan Putra (Ecopreneur.12, 2023)
Our research aims to determine the effect of compensation and job satisfaction on the loyalty of employees working in companies or industries in the city of Surabaya. The method used is the literature review methodÂ  by taking library data from the results of previous research. The target of the research we used was employees working in the city of Surabaya. The results obtained from this study can be used as insight and information to determine the effect of compensation provided by the company and employee job satisfaction on the loyalty that employees have to the company. The results of this study found that there is an influence of compensation and job satisfaction on employee loyalty to companies in the city of Surabaya so that the company needs to provide commensurate compensation and comfort that creates job satisfaction so that employees can be loyal to the company. Â Keywords: Employee, job satisfaction, compensation, loyalty, human resourcesÂ